2018
DOI: 10.2495/ei-v1-n2-183-192
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gaseous NO2 on p. fluorescens strain in the membrane adaptation and virulence

Abstract: Nowadays air pollution is increasing due to anthropogenic activity. Among all air pollutants, nitrogen oxides (NOx) such as NO 2 are predominant. It is well known that those compounds exhibit direct toxic effects on human health. However, microorganisms are also exposed to them, but the effect of NOx on the virulence of air microbiota is still poorly understood. In this study, we evaluated the impact of NO 2 on the adaptability and virulence of an airborne strain of P. fluorescens, MFA76a, by exposition of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

6
0

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…Nowadays, many QS autoinducers, such as the N‐acyl homoserine lactones (AHL) and quinolones (Gram‐negative bacteria) [ 5 ] and linear or cyclic peptides (Gram‐positive bacteria) [ 6 ] or furanosyl autoinducer 2, [ 7 ] produced by both type of microorganisms have been identified. Some species would also communicate through volatile organic compounds (nitrogen oxides) [ 8 ] and/or specific needle‐like structures (type VI secretion system). [ 9 ] Within natural microbiota, the bacterial chat is intense and modulated by degradation enzymes as AHL‐lactonases‐acylases, or peptidases, targeting specific QS factors through a mechanism designated as “Quorum Quenching.” [ 10 ] In parallel, bacteria also communicate with eukaryotic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, many QS autoinducers, such as the N‐acyl homoserine lactones (AHL) and quinolones (Gram‐negative bacteria) [ 5 ] and linear or cyclic peptides (Gram‐positive bacteria) [ 6 ] or furanosyl autoinducer 2, [ 7 ] produced by both type of microorganisms have been identified. Some species would also communicate through volatile organic compounds (nitrogen oxides) [ 8 ] and/or specific needle‐like structures (type VI secretion system). [ 9 ] Within natural microbiota, the bacterial chat is intense and modulated by degradation enzymes as AHL‐lactonases‐acylases, or peptidases, targeting specific QS factors through a mechanism designated as “Quorum Quenching.” [ 10 ] In parallel, bacteria also communicate with eukaryotic cells.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we showed slight modifications in the phospholipid composition of P. fluorescens MFAF76a membranes after exposure to NO 2 , including the disappearance of a minor unknown glycerophospholipid (UGP), but no lipid peroxidation seems to take place 33 . These previous results combined with the observed membrane alterations noted in Fig.…”
Section: Resultsmentioning
confidence: 80%
“…Therefore, the fluorescence polarization is proportional to the fluidity of the lipid bilayer in which the probe is inserted 31 , 32 . DPH behavior can also be affected by its ratio to lipids, but previous gas chromatography analysis did not show any difference in terms of quantity, composition and cis/trans ratio of fatty acid between the two conditions 33 . Our results showed that fluorescence anisotropy was significantly reduced to 0.192 after bacterial exposure to NO 2 (45 ppm) as compared to 0.217 for control condition (synthetic air), indicating an increased membrane fluidity (Fig.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…In contrast, a direct gaseous NO 2 exposure could also be benefit in the struggle against undesirable microorganism because it seems to impact their metabolism, social behavior, and growth [84]. Moreover, a continuous high-dose NO 2 exposure seems to lead in membrane alteration through an increased permeability [98].…”
Section: The Novel Therapeutic Strategies Mediated By Noxmentioning
confidence: 99%